Digital neutron-gamma discrimination in a wide energy range using pulse reconstruction method. (April 2015) - Jamili, S.; Bayat, E.; Afarideh, H.; Abbasi Davani, F.; Ghal-Eh, N.
Abstract: In this research, based on pulse reconstruction method, digital storage oscilloscopes with an 8-bit digital-to-analog convertor was used to successfully perform the neutron-gamma discrimination with NE213 (or its equivalent BC501A) scintillator anode pulses at minimum discrimination bias value of 95 keVee (or keV electron equivalent). Also, a 100 mCi 241 Am–Be source and micro-Curie gamma ray sources ( 137 Cs and 22 Na) were used for the system calibration and discrimination studies. The results confirm the feasibility and simplicity of the proposed method. Highlights: The pulse reconstruction method was utilized to perform neutron-gamma discrimination (NGD) with NE213 scintillator. A digital storage oscilloscope with an 8-bit digital-to-analog convertor was responsible for receiving the scintillator anode pulses. The NGD results on an Am–Be combined neutron-gamma source represents the feasibility of the proposed method.